The Economic Burden of Brain Disability in Korea, 2008-2011 - Hyun-Jin Kim PhD; Seung Hee Ho PhD; Sol Lee MPH; In-Hwan Oh MD, PhD; Ju Hee Kim MPH; Eun Joo Kim MD; Seong Jae Lee MD, PhD (SAGE Publishing, 2020)
This study estimated the economic burden of people with brain disability in Korea during 2008-2011 using nationally representative data and was conducted to use the results as an evidence for determining the resources allocation of people with brain disability. We used a prevalence-based approach to estimate the economic burden, classified by direct costs (medical costs and nonmedical costs) and indirect costs (productivity loss of morbidity and premature death). Data from the National Health Insurance Service, the National Disability Registry, the National survey on persons with disabilities, the Korea National Statistical Office's records of causes of death, and the Labor Statistics were used to calculate direct and indirect costs. The treated prevalence of brain disability increased from 0.26% (2008) to 0.35% (2011). Total economic burden of brain-related diseases was US$1.88 billion in 2008 and increased to US$2.90 billion in 2011, with a 54% rate of increase. The economic burden of all diseases, which was 1.2 to 1.4 times higher than that of brain-related diseases, accounted for US$2.61 billion in 2008 and US$3.62 billion in 2011, increasing by 39%. Owing to the growing occurrence of brain disability, the annual prevalence and related costs are increasing. Health management programs are necessary to reduce the economic burden of brain disability in Korea.